Encyclopedia of Life Sciences 2009
DOI: 10.1002/9780470015902.a0021754
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of mi RNA ‐mediated Gene Regulation in Mammals

Abstract: Micro ribonucleic acids (miRNAs) are a class of small noncoding RNAs, which are involved in a range of physiological and pathological processes. All animal miRNAs share common genomic structure, biosynthetic pathways and reaction mechanisms but mammals seem to have more miRNAs to match their organism complexity and longer 3′‐UTR (untranslated region) to evaluate more miRNA target sites. During the episode of miRNA innovation observed at the vertebrates to the placental mammals, mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 84 publications
(101 reference statements)
0
2
0
Order By: Relevance
“…The first miRNA, named Lin-4, was identified in 1993(Lee et al, 1993 and miRNAs have subsequently been shown to be present in a wide variety of species from single-cell algae to humans. Phylogenetically, this class of molecule emerged before the diversification of unicellular to multicellular organisms and may, therefore, be envisaged as a primal, critical and necessary regulatory mechanism present throughout evolution (Zhang and Lv, 2001;Cai et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first miRNA, named Lin-4, was identified in 1993(Lee et al, 1993 and miRNAs have subsequently been shown to be present in a wide variety of species from single-cell algae to humans. Phylogenetically, this class of molecule emerged before the diversification of unicellular to multicellular organisms and may, therefore, be envisaged as a primal, critical and necessary regulatory mechanism present throughout evolution (Zhang and Lv, 2001;Cai et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…At the evolutionary level, the complexity of an organism correlates well with the number of miRNAs expressed. Mammals express the highest number of miRNAs (Zhang and Lv, 2001) with the human genome capable of expressing $ 1000 miR-NAs with tissue and cell specificity (O'Connell et al, 2012). miRNAs have the potential to target more than one hundred mRNAs and may therefore affect several biological pathways simultaneously (He and Hannon, 2004).…”
Section: Introductionmentioning
confidence: 99%